Matched fundraising: evidence from a natural field experiment - Steffen Huck; Imran Rasul (Institute for the Study of Labor (IZA), 2010)
We present evidence from a natural field experiment designed to shed light on the efficacy of fundraising schemes in which donations are matched by a lead donor. In conjunction with the Bavarian State Opera House, we mailed 14,000 regular opera attendees a letter describing a charitable fundraising project organized by the opera house. Recipients were randomly assigned to treatments designed to explore behavioral responses to linear matching schemes, as well as the mere existence of a substantial lead donor. We use the exogenous variation in match rates across treatments to estimate the price elasticities of charitable giving. We find that straight linear matching schemes raise the total donations received including the match value, but partially crowd out the actual donations given excluding the match. If charitable organizations can use lead gifts as they wish, our results show they maximize donations given by simply announcing the presence of a lead gift. We contrast our price elasticity estimates with those based on changes in rules regarding tax deductions for charitable giving, as well as from the nascent literature using large-scale natural field experiments on giving.
Keywords: C93; D12; D64; 330; charitable giving; matched fundraising; natural field experiment